The Effectivity of Ethanol Extract of Datura Metel L. Seeds as a General Anaesthesia on Kintamani Dogs - I Putu Juli Sukariada; I Wayan Sudira; I Gusti Ngurah Sudisma (Udayana University, 2016)
This study aimed to determine the effectivity of ethanol extract of Datura metel L. seeds, as general anaesthesia on Kintamani dogs. A total of 25 dogs was divided into 5 groups, namely: group 1(treated by the combination of xylazin 1 mg/kg BW and ethanol extract of 10% Datura metel L. seeds 10 mg/kg BW), group 2 (treated by the combination of xylazin 1 mg/kg BW and ethanol extract of 10% Datura metel L. seeds 15 mg/kg BW), group 3 (treated by the combination of xylazin 1 mg/kg BW and ethanol extract of 10% Datura metel L. seeds 20 mg/kg BW), group 4 (treated by the combination of xylazin 1 mg/kg BW and ketamine 15 mg/kg BW), and group 5 (treated by the ethanol extract of 10% Datura metel L. seeds 15 mg/kg BW). Induction time, duration and recovery time were recorded, in which these responses were observed by clamping on the tail, ears and interdigital area. Physiological responses including respiration values, rectal temperature, oxygen saturation (SPO2), the frequency of the heart rate and electrocardiogram were observed using physiographic machine every 5 minutes until the dogs regain their consciousness. The level of ALT and AST was also examined to determine the level of toxicity of ethanol extracts of 10% Datura metel L. seeds. The results showed that group 1 and group 2 had no significant effect on the physiological response changes. However, the group 3 showed the sign of acute toxicity followed by increasing the levels of ALT and AST. The group 4 showed a decreasing physiological response, while group 5 had a similar response to group 2, but without sedation effect. It can be concluded that the ethanol extract of 10% Datura metel L. seeds has a potential as an analgesic and an anaesthetic agent.